Hypermedia APIs for the Web of Things - Martins, Jaime (2018)
The Web of Things is a new and emerging concept that defines how the Internet of Things can be connected using common Web technologies, by standardizing device interactions on upper-layer protocols. Even for devices that can only communicate using proprietary vendor technologies, upper-layer protocols can generally provide the necessary contact points for a high degree of interoperability. One of the major development issues for this new concept is creating efficient hypermedia-enriched application programming interfaces (APIs) that can map physical Things into virtual ones, exposing their properties and functionality to others. This paper does an in-depth comparison of the following six hypermedia APIs: 1) the JSON Hypertext Application Language from IETF; 2) the Media Types for Hypertext Sensor Markup from IETF; 3) the Constrained RESTful Application Language from IETF'; 4) the Web Thing Model from Evrythng; 5) the Web of Things Specification from W3C; and 6) the Web Thing API from Mozilla.